The stability of fine particle components of nickel laterite ore in aqueous suspension - Cortes, Micah Jane O. (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
This study aims to determine the stability of fine minerals as single component, two-component, and three-component systems in dilute aqueous environments as a function of pH and electrolyte concentration. The fine minerals investigated are silica (ave. diam. of 1.514 um), hematite (ave. diam. of 0.351 um), and nickel oxide (ave. diam. of 1.426 um). The zeta- potentials of silica, hematite, and nickel oxide minerals are measured using the micro-electrophoresis method at different pH and concentrations of KNO3, as supporting electrolyte. The Hamaker constant of each of the minerals in aqueous medium is determined by obtaining their respective critical coagulation concentration (c.c.c) at their stable pH conditions and at various concentrations of KNO3. The iso-electric points (i.e.p) for silica, hematite, and nickel oxide particles are determined to be at pH 2, pH 7.0, and pH 8.2, respectively. Hamaker constants of silica, hematite, and nickel oxide particles in aqueous media are likewise found to be 1.460 x 10-14 ergs, 1.657x10-13 ergs, and, 1.299 x 10-13 erg, respectively. The stabilities of the different component systems in aqueous suspension are monitored for 24 hours and the stability behavior are quantified by getting the heights of compression of the suspensions against pH and electrolyte concentrations (0. 01M, 0.001M, ad 0.0001 M KN03). The stability behaviors of these systems are described as following: 1. Single-component system (silica, hematite, and nickel oxide): a. Silica dispersion is stable at pH range 3- 11 and unstable near its i.e.p of pH 2.; b. Hematite dispersion is stable at pH 2-5 and pH 8-11, and unstable near its i. e.p of pH 7; c. Nickel oxide dispersion is stable at pH range 10-11 and unstable at pH 3-9, its i.e.p. located at pH 8.2. -- 2. Two-component systems (silica- hematite, silica- nickel oxide, and hematite - nickel oxide): a. Hematite-silica dispersion is stable at pH range 6-11 and unstable at pH range 3-5; b. Hematite-nickel oxide dispersion is stable at pH range 3-4 and 10-11 and unstable at pH range 5-9; c. Silica-nickel oxide dispersion is stable at pH range 10-11 and unstable at pH range 3-9. -- 3. Three-component system (silica-hematite-nickel oxide): Hematite-silica-nickel oxide dispersion is stable at pH range 10-11 and unstable at pH range 3-9. Increasing the electrolyte concentration decreases the magnitude of the zeta potential and decreases the stability of dispersions. It is worth noting, however, that the stability of laterite ore in aqueous environmenl is similar wilh that of the three-component system. Results of stability of the various components in aqueous environment are analyzed using the classical DLVO theory. This study attempts to elucidate the behavior of nickel laterite ores in aqueous suspension and establish a basis to develop a separation condition to recover one or two mineral components from the bulk laterite ores.
Thesis (M.S. Metallurgical Engineering)--University of the Philippines, Diliman.
Keywords: Nickel ores; Laterite; Aqueous suspension